2020
DOI: 10.11609/jott.6110.12.10.16272-16278
|View full text |Cite
|
Sign up to set email alerts
|

Records of two toads Duttaphrynus scaber and D. stomaticus (Amphibia: Anura: Bufonidae) from southeastern India

Abstract: We document two toad species Duttaphrynus scaber and D. stomaticus from southeastern India, in the Coromandel Coastal Plains.  Owing to incorrect data presented in previous reports denoting the occurrence of these toad species, their occurrence in the said region has remained obscure.  Our results, presented here, on both the species are based on morphological data from 15 preserved voucher specimens and direct field observations made by the authors in situ.  In this work, we report D. scaber from Chengelpet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The species were also found in secondary forest patches adjacent to human settlements. Ganesh et al (2020) reported this species as D. stomaticus from Tuticorin, Tamil Nadu. ZMUC 131366 [ex 199] from "Hoogly," ZMUC 131363 [ex 193] from "Calcutta," and ZMUC 131364 [ex 194] from "Calcutta."…”
Section: Taxonomic Accountsmentioning
confidence: 98%
See 4 more Smart Citations
“…The species were also found in secondary forest patches adjacent to human settlements. Ganesh et al (2020) reported this species as D. stomaticus from Tuticorin, Tamil Nadu. ZMUC 131366 [ex 199] from "Hoogly," ZMUC 131363 [ex 193] from "Calcutta," and ZMUC 131364 [ex 194] from "Calcutta."…”
Section: Taxonomic Accountsmentioning
confidence: 98%
“…Hence, records of D. stomaticus from Peninsular India (south of Maharashtra and possibly Odisha) are currently presumed to be doubtful and will require verification of all known populations (see D. peninsularis for discussion). The reports of D. stomaticus from Karnataka and Tamil Nadu States (Hegde 2012;Ramachandra et al 2012;Seshadri et al 2012;Ganesh et al 2020) likely refer to D. peninsularis. A report of D. olivaceus from Gurgaon, India (Ray and Deuti 2008) is also questionable (Heydari and Rastegar-Pouyani 2010) and considered to represent D. stomaticus based on our fresh collections from Delhi and surrounding North Indian regions.…”
Section: Duttaphrynus Stomaticus (Lütken 1864)mentioning
confidence: 99%
See 3 more Smart Citations